The Effect of Price and Product Quality on Customer Loyalty with Customer Satisfaction as a Mediating Variable: Case Study at Luargaris Coffee & Kitchen - Nanik Lestari; Dian Primariesta Sahara (Pusat P2M Politeknik Negeri Batam, 2025)
This research investigates how price and product quality influence customer loyalty, with customer satisfaction acting as a mediating variable, focusing on Luargaris Coffee & Kitchen. A quantitative approach was employed, using purposive sampling, and the study involved 372 respondents. This research primarily relies on primary data, which was gathered directly from participants who are consumers of Luargaris Coffee & Kitchen. The primary data was obtained through a carefully structured questionnaire designed specifically to address the research objectives. The dependent variable in this study is consumer loyalty, while the independent variables are price and product quality. Additionally, consumer satisfaction serves as the intervening variable. The data were analyzed through multiple linear regression, applying the SEM-PLS technique. The results indicate that product quality positively and significantly affects customer loyalty, mediated by customer satisfaction. In contrast, price and service quality did not show a significant impact on customers’ purchasing decisions. The findings highlight the importance of prioritizing product quality improvement as a fundamental strategy to enhance long-term customer satisfaction and foster customer loyalty.